Filter media for stormwater treatment and recycling: the influence of hydraulic properties of flow on pollutant removal - Hatt, B.E.; Siriwardene, N.; Deletic, A.; Fletcher, T.D. (Water Science and Technology, 2006)
Improved urban water management in Australia is of national importance. Water resources are stretched and urban runoff is a recognized leading cause of degradation of urban waterways. Stormwater recycling is an option that can contribute to easing these problems. Biofilters are effective structural stormwater pollution control measures with the potential for integration into stormwater treatment and recycling systems. However, premature clogging of biofilters is a major problem, with resulting decreased infiltration capacity (and hence the volume of stormwater the system can detain) and increased detention time. This paper presents preliminary findings with respect to the effect of clogging on pollutant removal efficiency in conventional stormwater filter media. A one-dimensional laboratory rig was used to investigate the impact of clogging on pollutant removal efficiency in a conventional biofiltration filter media (gravel over sand). Both the individual gravel layer and the overall multi-filter were highly efficient at removing suspended solids and particulate-associated pollutants. This removal efficiency was consistent, even as the filters became clogged. Removal of dissolved nutrients was more variable, with little reduction in concentrations overall. Although preliminary, these results challenge the concept that increased detention time improves the treatment performance of stormwater filtration systems.